15 FACTORS RELATED TO SATISFACTION WITH CARE AMONG A SAMPLE OF HEAD START PARENTS. (1st January 2006) - Patel, P.; Bazargan-Hejazi, S.; Tataw, D.; Kima-Johnson, S.
Abstract : Objective: To identify factors related to satisfaction with health care provider among a sample of Head Start parents. Design: A retrospective study. Sample: 250 consented parents/guardians of registered Head Start children from four Head Start sites in South Central Los Angeles. Study Hypotheses: (1) Parents who report a higher level of satisfaction in the communication with their child's health care provider are significantly more likely to report higher levels of satisfaction with the health care. (2) Parents who report the ability to voice their opinion to their child's health care provider are significantly more likely to report a higher level of satisfaction with care. (3) Parents who report higher levels of trust with their child's provider are significantly more likely to report higher levels of satisfaction with care. Study Measures: Selection of study variables followed the Behavioral Model for Vulnerable Populations including variables such as accessibility to medical care; affordability of medical care; availability of health related information; ability to voice one's concern; regular sources of care; knowledge of location and direction to health care services; satisfaction with doctor, and trust. Results: From a list of 12 potential covariates, only ability to voice one's opinion ([OR & 95% CI = 1.24 (1.14-1.36)] and having insurance [OR & 95% CI = 1.73 (1.06-2.84)] remained statistically significant to explain variation in satisfaction with health care provider. Discussion: Findings of this study shed lights on the importance of interventions to empower parents/guardian to voice their concerns about their child's health to providers.